UbiGate: a synthetic biology toolbox to analyse ubiquitination. Issue 4 (30th November 2017) - Kowarschik, Kathrin; Hoehenwarter, Wolfgang; Marillonnet, Sylvestre; Trujillo, Marco
Summary: Ubiquitination is mediated by an enzymatic cascade that results in the modification of substrate proteins, redefining their fate. This post‐translational modification is involved in most cellular processes, yet its analysis faces manifold obstacles due to its complex and ubiquitous nature. Reconstitution of the ubiquitination cascade in bacterial systems circumvents several of these problems and was shown to faithfully recapitulate the process. Here, we present UbiGate − a synthetic biology toolbox, together with an inducible bacterial expression system – to enable the straightforward reconstitution of the ubiquitination cascades of different organisms in Escherichia coli by 'Golden Gate' cloning. This inclusive toolbox uses a hierarchical modular cloning system to assemble complex DNA molecules encoding the multiple genetic elements of the ubiquitination cascade in a predefined order, to generate polycistronic operons for expression. We demonstrate the efficiency of UbiGate in generating a variety of expression elements to reconstitute autoubiquitination by different E3 ligases and the modification of their substrates, as well as its usefulness for dissecting the process in a time‐ and cost‐effective manner.